Spatial Localization of Sound in Early Blind During Spatial Bisection Task and Minimum Audible Angle Task (International Journal of Physiology, 2019)
BackgroundResearch has shown that early blind have supra-normal localization abilities in the azimuthal plane while performing a minimum audible angle task which is based on egocentric paradigm. An opposing view has been proposed that the early blind have a deficit in spatial localization of sound in the horizontal plane during an allocentric based task such as spatial bisection of sound. The objective of our study was to assess spatial localization of sound in the early blind by means of minimum audible angle task and spatial bisection task.MethodsA total of ten early blind and ten normal sighted blind folded controls were subjected to minimum audible angle task and spatial bisection task in the azimuthal plane.ResultsThe early blind subjects performed significantly poorer than controls in the spatial bisection task which was based on the allocentric model. However, they performed as well as the controls in the Minimum audible angle task which was based on egocentric model.ConclusionThe minimum audible angle task based on the egocentric paradigm does not require a metric representation of auditory space whereas allocentric paradigm based task would require the same. However the spatial bisection task which is based on the allocentric paradigm taxes the retinotopic maps. Hence the poor performance in this task